Development of Silika-Alumina Matrix as Cracking Catalyst Component - Lutfi Widikrama, Candra
The need for fuel oil (BBM) continues to increase along with economic growth, population, energy and policies that have been determined by the government. Fuel consumption is predicted to increase. To compensate for the fuel supply, required efforts to fulfill its needs.Fluid Catalytic Crancking (FCC) is one of the methods that can fulfill the requirement of gasoline because FCC can increase gasoline recovery from heavy fraction of the distillation column. The FCC catalyst component is the zeolite, matrix, filler, and binder. The heavy fraction of the distillation column has a large particle size so that it cannot diffuse into zeolite pores. Therefore it is necessary to do research on the synthesis of active matrix FCC catalyst components. This research aims to study the relationship between Si/Al ratio and the addition of phosphorus to the physical properties and activity of the active silica-alumina matrix. The matrix active is synthesized by the method developed by Catalyst and Reaction Engineering Laboratory, Bandung Insitute of Technology, which refers to US patent US 6723297 B2. Variations used are SiO2 compositions of 50%-b, 60%-b, 70%-b, 75%-b, and 80%-b. In addition, variations in the addition of phosphorus by 1%-b and 2%-b were also carried out. Furthermore, the physical properties of the active matrix were characterized by the BET method to obtain specific surface area, pore diameter and specific pore volume. The total acidity and type of acid site on the active matrix were characterized by NH3-TPD. The active matrix performance test was carried out using a microactivity test (MAT) with vacuum gas oil (VGO) as feed. The reaction product is analyzed using the gas chromatography method. The results showed that more silica composition, the average pore diameter of the matrix was enlarged while the specific surface area of the matrix tended to decrease. Similarly, the addition of phosphorus. The addition of silica and phosphorus also tends to reduce the similarity of the active matrix. The best matrix active activity was obtained for the variation of SAP1 75% -b SiO2 with the highest LCO gain of 33% -b.